IMPROVING STUDENTS’ VOCABULARY USE IN SPEAKING THROUGHT CONTEXT-BASED DRAWING ACTIVITIES - Lestari, Pinta; Yauri, Andi Muhammad; Ilmi HL, Siti Nurul (Jurnal Diskursus Islam, 2025)
This research aims to improve students' vocabulary use in speaking through context-based drawing activities. Many students at SMPN 3 Mare experience difficulties in understanding and using English vocabulary, especially nouns, verbs, and adjectives. This limitation hinders their ability to express ideas orally, understand teacher instructions, and participate confidently in classroom communication. Previous studies emphasize that speaking ability is strongly influenced by vocabulary mastery and that meaningful vocabulary learning must be contextualized to support real-life communication. Context-based drawing activities have been shown to increase students' engagement, creativity, and conceptual understanding by visualizing language in familiar contexts. Therefore, this study applies context-based drawing as a strategy to help students practice using vocabulary meaningfully while describing their drawings orally. Using a classroom action research design, data were collected through observations, speaking tests, and interviews. The results showed that the use of context-based drawing activities significantly improved students' recall, accuracy, and fluency in speaking. Students became more confident in constructing sentences and were better able to identify and use vocabulary according to its grammatical category. The results showed that context-based drawing activities were effective in creating a more engaging learning atmosphere and improving vocabulary use in speaking. This method can serve as an alternative learning strategy for English teachers to support active communication and meaningful vocabulary learning.